Serum uric acid on admission predicts in-hospital mortality in patients with acute coronary syndrome. (1st August 2017) - Magnoni, Marco; Berteotti, Martina; Ceriotti, Ferruccio; Mallia, Vincenzo; Vergani, Vittoria; Peretto, Giovanni; Angeloni, Giulia; Cristell, Nicole; Maseri, Attilio; Cianflone, Domenico
Abstract: Background: Despite the association between uric acid and cardiovascular disease has been known for decades, the prognostic value of serum uric acid (UA) in all clinical manifestations of acute coronary syndrome (ACS), namely ST-elevation myocardial infarction (STEMI), NSTEMI and unstable angina, has not been definitively assessed. Methods: This retrospective analysis included patients from previous SPAI and FAMI studies with the aim to investigate the association between serum uric acid and major adverse cardiovascular events at 180 days from hospital admission. Results: 1548 patients were considered and divided in four groups, according UA concentration. Uricemia was significantly associated with gender, BMI, arterial hypertension, HDL-cholesterol, triglycerides, metabolic syndrome and glomerular filtration rate in univariate analysis. Multivariate logistic regression indicated that UA > 6.0 mg/dL on admission increased the risk of in-hospital mortality in overall population (OR 2.9, 95%CI 1.4–6.1; p  = 0.0057) and in patients with de novo ACS (OR 3.2, 95%CI 1.5–6.8; p  = 0.0033). Comparable results were also obtained after adjusting the model for age, gender, body mass index, glomerular filtration rate, metabolic syndrome, acute revascularization and ethnicity. A positive correlation was observed between UA and C reactive protein concentrations in in-hospital deaths only (rho 0.41, p  = 0.027). Conclusion: In patients with acute coronary syndrome, uricemia levels above the current international reference limit (6.0 mg/dl) were associated with in-hospital mortality, independently from ethnicity and renal function.